Paradigma dalam Pembelajaran Sejarah Kontroversi - Sumardiansyah Sumardiansyah (Jurnal Pendidikan Sejarah, 2015)
After the fallen of the new order era, social-political structures has been supporting the born of new claims or interpretations towards the so-called-and-believed history. Some historical themes have been discussed, reviewed and re-narrated in new interpretation and perspective. This is marked with the issuance of new books, the emergence of new ideas, as well as findings of recent facts and data. This phenomenon has emerged with its pro and contra among historians, teachers and general society, then later leads to a new found term as controversial history.This article aims to discuss the paradigm of learning the controversial history study, that includes what is controversial history study itself, the urgency of historical learning, as well as models, approaches, and strategies used by teachers in the face of controversial history learning. Controversial history is an interesting theme in classroom history learning since it can stimulates learners to practice their logical, critical, and creative thinking. Full understanding and in-depth material for a history teacher is absolutely necessary here, other than the ability to manage learning in didactic-methodical. Research based methods used a qualitative approach, in which the resources obtained throught literature review.